Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada PT Free Time Kediri - Yongky Dwi Ariyanto; Ustadus Sholihin; Beny Mahyudi Saputra (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
This research aims to determine the influence between product quality and service quality on customer satisfaction at PT. Free Time Kediri. The research method used is a quantitative method with a descriptive approach. Data collection in this research was carried out by distributing questionnaires to PT customers. Free Time Kediri and calculated using the SPSS Version 25 application. Data analysis techniques used include Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test, and R2 Coefficient of Determination Test. In the Validity Test, it is known that all question items (X1, X2, and Y) have a significance value of 0.000 < 0.05 so that each variable is declared valid. Then in the Reliability Test each variable was declared reliable because it had a Cronbach's Aplha value > 0.60. Then in the t test it is known that the variables product quality (X1) and service quality (X2) have a significance value of 0.000 <0.05 so that these two variables partially have a significant effect on purchasing decisions (Y). Then the F test shows that the significance value is 0.000 <0.05, which shows that product quality and service quality simultaneously influence customer satisfaction at PT. Free Time Kediri.